A Method Based on Only Currents for Determining Fault Direction in Radial Distribution Networks Integrated with Distributed Generations - Khoa, Ngo Minh; Khoa, Tran Xuan (Proceedings of Engineering and Technology Innovation, 2021)
Nowadays, more distributed generations (DGs) are connected to a radial distribution network, so conventional overcurrent relays cannot operate correctly when a fault occurs in the network. This study proposes a method to determine the fault direction in a three-phase distribution network integrated with DGs. The obtained pre-fault and fault currents are utilized to extract their phasors by the fast Fourier transform, and the phase angle difference between the positive-sequence components of the pre-fault and fault currents is used. Moreover, the method only uses the local current measurement to calculate and identify the phase angle change of the fault current without using the voltage measurement. Matlab/Simulink software is used to simulate the three-phase distribution network integrated with DGs. The faults with different resistances are assumed to occur at backward and forward fault locations. The simulation results show that the proposed method correctly determines the fault direction.